1999
DOI: 10.1038/sj.cdd.4400515
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage and nuclear translocation of the caspase 3 substrate Rho GDP-dissociation inhibitor, D4-GDI, during apoptosis

Abstract: While investigating endonucleases potentially involved in apoptosis, an antisera was raised to bovine deoxyribonuclease II, but it recognized a smaller protein of 26 kDa protein in a variety of cell lines. The 26 kDa protein underwent proteolytic cleavage to 22 kDa concomitantly with DNA digestion in cells induced to undergo apoptosis. Sequencing of the 26 kDa protein identified it as the Rho GDPdissociation inhibitor D4-GDI. Zinc, okadaic acid, calyculin A, cantharidin, and the caspase inhibitor z-VAD-fmk, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 30 publications
4
43
0
Order By: Relevance
“…However, the function of RhoGDI2 cleavage has only recently been elucidated. Based on the observation that the expression of a non-cleavable RhoGDI2 D19A mutant did not protect CHO cells against apoptosis induction, it was concluded that RhoGDI2 cleavage does not contribute to cell death (22). By contrast, another study suggested that the cleavage of RhoGDI2 by caspase-3 is not a functionally irrelevant effect of caspase activation during apoptosis but rather expedites the progression of the apoptotic process (23).…”
Section: Discussionmentioning
confidence: 99%
“…However, the function of RhoGDI2 cleavage has only recently been elucidated. Based on the observation that the expression of a non-cleavable RhoGDI2 D19A mutant did not protect CHO cells against apoptosis induction, it was concluded that RhoGDI2 cleavage does not contribute to cell death (22). By contrast, another study suggested that the cleavage of RhoGDI2 by caspase-3 is not a functionally irrelevant effect of caspase activation during apoptosis but rather expedites the progression of the apoptotic process (23).…”
Section: Discussionmentioning
confidence: 99%
“…Such a localization of caspase-cleaved protein fragments to the nucleus is not uncommon, as we reported recently that the caspase-cleaved form of the Lyn tyrosine kinase is delocalized into the nucleus of cells undergoing apoptosis. 25 Moreover, several other caspase-derived fragments of substrates including FAK, 26 FHOD1, 27 Rho-GDI2, 28 YY1, 29 D4GDJ, 30 Huntingtin 31 and Beclin 1 32 are also targeted into the nucleus in identical circumstances. Of note in the present study, we clearly demonstrated that nuclear localization of DJ-1 Nt is essential for its pro-apoptotic function.…”
Section: Discussionmentioning
confidence: 99%
“…RelA (SC-109), Santa Cruz Biotechnology (Santa Cruz, CA); cytochrome c (clone 7H8.2C12) monoclonal, BD PharMingen (San Diego, CA); Bax (clone 2D2) monoclonal, Zymed Laboratories Inc. (San Francisco, CA); caspase-8 (AAP-118) polyclonal, StressGen Biotechnologies Corporation (Victoria, BC, Canada); p21 WAF1 (clone EA10) monoclonal, Oncogene Research Products (Boston, MA); the D4-GDI polyclonal antibody was developed in this laboratory (19); the Mcl-1 monoclonal antibody and the Bid monoclonal antibody were generously provided by Dr. R. Craig (Dartmouth Medical School, Hanover, NH) and Dr. X. Wang (HHMI, Dallas, TX), respectively. Unless otherwise specified, all other reagents were purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibitors-To assess the capacity of ML-1 cells to undergo apoptosis in response to TNF, cells were exposed to TNF in combination with either CHX or act D for 3 h. As an index of apoptotic activity, lysates were immunoblotted for D4-GDI cleavage, a marker of caspase-3 activation (19). A 3-h treatment with either TNF, CHX, or act D alone exhibited no evidence of apoptosis as measured by D4-GDI cleavage (Fig.…”
Section: Tnf Induces Apoptosis In the Presence Of Protein Or Rna Syntmentioning
confidence: 99%